The United States and Latin America (1920)
This book is based on a smaller volume issued by the Johns Hopkins Press in 1900 under the title "The Diplomatic Relations of the United States and Spanish America," which contained the first series of Albert Shaw Lectures on Diplomatic History. That volume has been out of print for several years, but calls for it are still coming in, with increasing frequency of late. In response to this demand and in view of the widespread interest in our relations with our Southern neighbors I have revised and enlarged the original volume, omitting much that was of special interest at the time it was written, and adding a large amount of new matter relating to the events of the past twenty years. (Tomado del texto)